(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Since there is a continuous rise in the number of patients requiring quantity of prescribed medications and medical care, there is always an increasing requirement for a complete system that can carefully evaluate all the medication errors that may occur. Objective: Determine types, causes, and barriers of medication errors report Setting: The current study was conducted in Imam Sadiq Hospital - Babel City during 2019 year Subjects: The study comprised of 100 nurses with at least two years of clinical experience Tools: The Medication Administration Errors (MAEs) method was used to gather the data by reporting ruestionnaire that was formulated by Wakefield et al.(1996) and revised by the researchers. The questionnaire has 65 questions; 15 items are related to the reasons of medication errors occurrence, 7 items concerning the reasons of not reporting medication errors and 5 items related to the percentage of each medication error type reported on units which classified into 9 items for non- intravenous and 11 items for intravenous medication administration errors. Results: most of nurses reported no mistakes related to wrong route, wrong dose, wrong method; Whilewrong time, allergic reaction and infusion rate mistakes were more repetitive errors according to their perception. Fears about punishmentand from patient relatives was most common barriers to report medicationerrors. Conclusion: Medication errors is highly priority health system problem; more than half of nurses reported no mistakes related to wrong dose, wrong method, and wrong patient, most of them indicated that no clearly definition of medication error was identified, unclear reporting system wasexisted. Recommendations Assessment and surveillance system should be followed to minimize medication errors potentiality. Nurses have to always remember that they are responsible and accountable to the results of their decisions andactions whatever they are.